Edukasi perawatan fleksibilitas dan keseimbangan tubuh pada lansia di Posyandu Lansia, Way Sulan Tanjung Bintang - Saputra, Rinaldi Prima; Zulfikar, Zulfikar; Fadhail, Maulana Ahsan (JOURNAL OF Public Health Concerns, 2025)
Background: Aging is a natural process that cannot be avoided by every individual. Aging is a process of gradual loss of the ability of tissue to repair itself or replace itself and maintain its normal structure and function. This decrease in physical capacity is caused by several factors including musculoskeletal, cardiovascular and neuromuscular factors. The occurrence of decreased physical capacity is a condition that is very common in society that can trigger pain. As much as 28-35% of elderly people over 65 years old fall at least once a year and increase at the age of over 75 years by 32-42%. So, it is very important for the elderly to maintain and maintain muscle strength. Purpose: Provide health education as an effort to increase knowledge about the importance of balance and flexibility in the elderly. Method: The implementation of this activity goes through several stages, namely asking for permission from the local primary health, namely the Way Sulan Health Center, explaining the importance of conducting education to the elderly and explaining the importance of knowledge/understanding of elderly health problems with specific discussions on balance and flexibility. In the implementation stage, all participants were given material presentations using lecture and presentation methods. This was followed by a discussion and question and answer session. Results: Based on the Time Up and Go Test examination of 70 participants, it shows that the majority of elderly people have a low risk of falling as many as 13 people (18.57%). As many as 24 elderly people (34.28%) are in the moderate risk of falling category and as many as 33 people (47.14%) have a greater risk of falling. And based on the Sit & reach test examination, it shows that the majority of elderly people have hamstring and lowerback flexibility ≥ 4 inches 16 people (22.85%). As many as 20 elderly people (28.57%) are in the flexibility category ≥ 3 inches, as many as 30 people (42.85%) with flexibility ≥ 2 inches and as many as 4 people have flexibility ≥ 1 inch (5.71%). Conclusion:  Health counseling or education for the elderly about balance and flexibility has a very good impact on the community, especially on the mechanism of managing elderly health that can be done independently or with family support. Educational programs about balance and flexibility also increase awareness of the importance of maintaining fitness, and being aware of the risk of falling in the elderly. .Keywords: Balance; Elderly; Flexibility; Health education Pendahuluan: Lanjut usia (lansia) merupakan proses alami yang tidak dapat dihindari oleh setiap individu. Penuaan (menjadi tua: aging) adalah suatu proses penghilangan secara perlahan-lahan kemampuan jaringan untuk memperbaiki diri atau mengganti diri dan mempertahankan struktur dan fungsi normalnya. Penurunan kapasitas fisik ini disebabkan oleh beberapa faktor diantaranya faktor penurunan muskuluskeletal, kardiovaskular dan neuromuskular. Kejadian penurunan kapasitas fisik merupakan kondisi yang sangat banyak dijumpai di masyarakat yang bisa memicu terjadinya rasa nyeri. Sebesar 28-35% lansia di atas 65 tahun setidaknya jatuh satu kali dalam satu tahun dan meningkat pada usia di atas 75 tahun sebesar 32-42%. Jadi, sangat penting bagi lansia untuk menjaga dan memelihara kekuatan otot. Tujuan: Memberikan penyuluhan kesehatan sebagai upaya meningkatkan pengetahuan mengenai pentingnya keseimbangan dan fleksibilitas pada lansia. Metode: Pelaksanaan kegiatan ini melalui beberapa tahapan yaitu meminta ijin kepada kesehatan primer setempat yaitu puskesmas Way Sulan menjelaskan kepentingan untuk melakukan penyuluhan kepada lansia dan menjelaskan pentingnya pengetahuan/pemahaman masalah kesehatan lansia dengan spesifik pembahasan keseimbangan dan fleksibilitas. Tahap pelaksanaan seluruh peserta diberikan pemaparan materi dengan metode ceramah dan presentasi. Selanjutnya dilakukan dengan sesi diskusi dan tanya jawab. Hasil: Berdasarkan pemeriksaan Time Up and Go Test  dari 70 peserta menunjukkan bahwa mayoritas lansia memiliki risiko jatuh kecil sebanyak 13 orang (18.57%). Sebanyak 24 orang lansia (34.28%) dalam kategori risiko jatuh sedang dan sebanyak 33 orang (47.14%) memiliki risiko jatuh lebih besar. Dan berdasarkan pemeriksaan Sit & reach test menunjukkan mayoritas lansia memiliki fleksibilitas hamstring dan lowerback ≥ 4 inch 16 orang (22.85%). Sebanyak 20 orang lansia (28.57%) dalam kategori fleksibilitas ≥ 3 inch,  sebanyak 30 orang (42.85%) dengan fleksibilitas ≥ 2 inch dan sebanyak 4 orang memiliki fleksibilitas ≥ 1 inch (5.71%). Simpulan: Penyuluhan kesehatan atau edukasi pada lansia tentang keseimbangan dan flesibilitas memberikan dampak yang sangat baik pada masyarakat, khususnya pada mekanisme pengelolaan kesehatan lansia yang dapat dilakukan secara mandiri atau oleh dukungan keluarga. Program edukasi tentang keseimbangan dan fleksibilitas juga meningkatkan kesadaran tentang pentingnya mempertahankan kebugaran, dan mewaspadai resiko jatuh pada lansia.